1985
DOI: 10.1037/0022-0663.77.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Further comparison of representational and transformational prose-learning imagery.

Abstract: Eighth-grade students read fictitious passages describing the accomplishments of "famous" people. Two different types of visual imagery instructions (representational and transformational) were manipulated within two different passage types (name and occupation), along with no-strategy control instructions for each passage type. Consistent with theoretical predictions, transformational imagery instructions were uniquely effective on the difficultto-remember name passages, but not on the more easily represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There is also evidence that children of this age do not induce imagery but need to be instructed directly in its use (Oakhill and Patel, 1991), and that not all types of imagery training result in enhanced reading comprehension (Levin, 1973). It appears, for example, that representational imagery, or the fairly direct translation of text into visual images, may be more efficient for the comprehension of narrative text, whereas transformational imagery training may be more appropriate for expository text (Peters, Levin, McGivern and Pressley, 1985). The latter form of imagery training, where some aspects of the text are transformed so that images do not correspond directly to the text, would seem to be more appropriate for children reading non-narrative texts containing difficult to remember information that does not lend itself easily to simple visual representation.…”
Section: Reading Comprehension and Visual Imagery Trainingmentioning
confidence: 99%
“…There is also evidence that children of this age do not induce imagery but need to be instructed directly in its use (Oakhill and Patel, 1991), and that not all types of imagery training result in enhanced reading comprehension (Levin, 1973). It appears, for example, that representational imagery, or the fairly direct translation of text into visual images, may be more efficient for the comprehension of narrative text, whereas transformational imagery training may be more appropriate for expository text (Peters, Levin, McGivern and Pressley, 1985). The latter form of imagery training, where some aspects of the text are transformed so that images do not correspond directly to the text, would seem to be more appropriate for children reading non-narrative texts containing difficult to remember information that does not lend itself easily to simple visual representation.…”
Section: Reading Comprehension and Visual Imagery Trainingmentioning
confidence: 99%
“…Though visual mental imagery training has been shown to facilitate reading comprehension in many studies, other research has shown an inconsistent effect of imagery training on comprehension in some situations (Moore & Kirby, 1988; Oakhill & Patel, 1991; Peters, Levin, McGivern, & Pressley, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…, see Mastropieri, Scruggs, & Levin, 1986; Scruggs, Mastropieri, McLoone, Levin, & Morrison, 1987), improving eighth graders' prose comprehension (Peters, Levin, McGivern, & Pressley, 1985), and teaching vocabulary words to educable mentally retarded (EMR) junior high school students (Scruggs et al . , 1985) and LD sixth graders (Condus, Marshall, & Miller, 1986).…”
mentioning
confidence: 99%